2021
DOI: 10.21608/zjfm.2021.61072.1070
|View full text |Cite
|
Sign up to set email alerts
|

Amylase and Lipase Enzymes as Factors Affecting Acute Organophosphorous Poisoning Morbidity and Mortality

Abstract: The organophosphorous insecticides (OPIs) is widely used. The toxicity of OPIs is related to many biochemical disorders, for example changes in serum amylase and lipase enzymes. Average duration of admission affects prognosis of poisoning severity and outcome. The aim of this work was to evaluate the role of average days of admission, serum amylase and lipase enzymes in assessing OPIs poisoning severity, outcome, and complications in acutely OPIs poisoned patients admitted to Poison control center at Zagazig U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…This was in agreement with Samy et al (2018), Eisa et al (2021) and who reported that the POP scale's severity and days of admission had a statistically significant relationship. Twayana et al (2019) noticed that the correlations of POP scale with lag time and atropinization dose, showed no statistical significance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This was in agreement with Samy et al (2018), Eisa et al (2021) and who reported that the POP scale's severity and days of admission had a statistically significant relationship. Twayana et al (2019) noticed that the correlations of POP scale with lag time and atropinization dose, showed no statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…Samy et al (2018) reported that there were no statistical significance differences with respect to age and gender distribution between severe and moderate poisoning. On the contrary, Eisa et al (2021) reported that there was statistically significant relation between age of the studied patients and route of exposure with severity according to POP scale.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation